The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.12816/0000251
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dermestes Maculatus ( DeGeer , 1774 ) ( Coleoptera , Dermestidae ) on Different Fish Substrates

Abstract: The development of Dermestes maculatus (DeGeer) on four smoked fish substrates [Trigger fish (Balistes capriscus), Catfish (Synodontis sp.), African catfish (Clarias gariepinus) and Nile Tilapia (Oreochromis niloticus)] were investigated as completely randomized design under laboratory temperature of 30 o C, relative humidity of 65±5% and a light: darkness regimen of 12:12 hours. Females laid eggs within 24 hours of copulation. The numbers of eggs laid and the period between larval instars were not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
15
1
1
Order By: Relevance
“…Differences in weights of male and female beetles that developed in different substrates were observed in earlier studies (Danho et al, 2002;Zakka, 2005). The improved variety ADV NCRE-STR that proved relatively resistant to the pest had heavier adults emerging from it; this could be due to its ability to supply nutrients that can encourage robust physical development of the pest but possibly possesses an inhibitory factor that perhaps affects oviposition, larval or pupal development.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Differences in weights of male and female beetles that developed in different substrates were observed in earlier studies (Danho et al, 2002;Zakka, 2005). The improved variety ADV NCRE-STR that proved relatively resistant to the pest had heavier adults emerging from it; this could be due to its ability to supply nutrients that can encourage robust physical development of the pest but possibly possesses an inhibitory factor that perhaps affects oviposition, larval or pupal development.…”
Section: Discussionmentioning
confidence: 63%
“…The fourteen hybrid varieties were obtained from the International Institute of Tropical Agriculture (IITA), Ibadan germplasm, while the three local cultivars were purchased from open markets in Ali-Brada and Mile 3 both in Rivers State, Nigeria. The experimental jars and maize varieties were all sterilized thermally in a hot-air Gallenkamp oven at 60ºC for 2 hours to kill any pest and pathogen that might be present and allowed to acclimatize for 24 hours to laboratory temperature (30ºC) in the laboratory (Atijegbe, 2004;Zakka, 2005). S. zeamais culture was raised in the laboratory from infested maize collected in Choba market in Rivers State and reared on a susceptible local maize variety (Coma) in 1-Litre Kilner jars which were left on an open air shelf in the laboratory.…”
Section: Laboratory Screening Of Maize Varieties Against S Zeamais Imentioning
confidence: 99%
See 1 more Smart Citation
“…Females demonstrated a strong preference for ovipositing into the fur substrate as opposed to the paper or no cover situations, both in terms of the total number of progeny produced and in the rate of progeny per female. Though other studies have reported fresh or smoked fish as a diet and oviposition substrate for D. maculatus (Ezenwaji and Obayi, 2004;Zakka et al, 2013), this study used commercially available pet food as a diet with a separate oviposition substrate to facilitate the collection of individuals for bioassays. The advantages of using the dog food were that it is inexpensive, easy to obtain, does not have an objectionable odor and is shelf-stable.…”
Section: Resultsmentioning
confidence: 99%
“…Human food products that D. maculatus infests include dried fish (Osuji, 1975;Zakka et al, 2013), milk powders and cheese (Rajendran and Parveen, 2005) and mophane larvae (also known as phane) (Mpuchane et al, 2000). D. maculatus also infests durable goods such as hides, woolen materials (Rajendran and Parveen, 2005) and silkworm cocoons (Veer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%